Clustering and decoherence of correlated spins under double quantum dynamics - Sánchez, Claudia Marina (2014)
We present a new approach for the study of the evolution of spin correlations and decoherence in multiple quantum Nuclear Magnetic Resonance experiments. The infinite system, constituted by the protons of a polycrystalline Adamantane sample, evolves under a double quantum Hamiltonian. The distribution of multiple quantum coherence orders is represented by a contribution of spin clusters with different sizes that exchange spins, increasing their size with the evolution time. A cluster with nearly exponential growth at all times is observed, in agreement with previous models. Remarkably, a small cluster that stabilizes in a size corresponding to 18 correlated spins is revealed. In addition, by performing a renormalization of the obtained data with the experimental Loschmidt Echo, the contribution of the different clusters to the observable signal is determined. This procedure accounts for the effect of the decoherence on the evolution of the system, and allows to set the range of confidence of the experimental data. Our analysis confirms the natural hint that, correlated states involving higher coherence orders are far more sensitive to the uncontrolled decoherent interactions, than those involving lower orders.